Comparing the Hem- and Lymphangiogenic Profile of Conjunctival and Uveal Melanoma Cell Lines - Refaian, Nasrin; Schlereth, Simona L.; Koch, Konrad R.; Notara, Maria; Hos, Deniz; Mescher, Melina; Iden, Sandra; Bosch, Jacobus J.; Jager, Martine J.; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2015)
Malignant melanomas of the ocular surface (conjunctival melanoma [CM]) and within the eye (uveal melanoma [UM]) show different types of metastatic behavior. While CM has a propensity to spread first to regional lymph nodes, UM metastasizes almost exclusively via the hematogenic route to the liver. We investigated whether these different metastatic patterns might be attributable to differential hem- and lymphangiogenic characteristics of CM and UM cells.Human CM (CM2005.1, CRMM1, CRMM2) and UM (Mel270, Mel290, OM431) cell lines were analyzed for VEGF-A, -C, and -D expression by RT-PCR and ELISA. The influence of CM- or UM-conditioned medium on blood (BEC) and lymphatic (LEC) endothelial cell proliferation and migration was measured using 3-[4,5-dimethylthiazol-2yl]-2,5-diphenyl-tetrazolium bromide (MTT) and scratch assays, respectively.Vascular endothelial growth factor-A, -C and -D mRNA, and VEGF-A and -D protein were expressed by all CM and UM cell lines, while VEGF-C protein was only expressed by UM cell lines. The CM- and UM-conditioned medium did neither differentially affect BEC (P = 0.86) and LEC (P = 0.90) proliferation, nor BEC (P = 0.56) and LEC (P = 0.90) migration.Conjunctival melanoma cell lines did not show a higher prolymphangiogenic potential, and UM cell lines did not show a higher prohemangiogenic potential. Accordingly, other mechanisms within the tumor microenvironment might account for the diverging metastatic patterns of conjunctival versus uveal melanomas.
EVALuna2:25718